Systematic Literature Review: Analysis of Students' Reasoning Ability and Difficulties in Newton's Law Material - Nur Azizah; Lia Yuliati; Khusaini (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify students' reasoning abilities and learning difficulties related to Newton's Laws through a systematic literature review using the PRISMA method. The review analyzes seven scientific articles published between 2020 and 2024 in SINTA-accredited journals, international conference proceedings, and Scopus-indexed sources. The findings indicate that students’ reasoning abilities regarding Newton's Law are still low, with an average conceptual understanding of only 33.3%. Common difficulties faced by students include interpreting Newton's First Law (inertia and constant velocity), understanding the relationship between force, mass, and acceleration in the Second Law, and the action-reaction principle in the Third Law. These difficulties are generally caused by the abstract nature of the concepts and students’ weak logical reasoning skills. The review also highlights the need for effective instructional strategies. Contextual teaching, problem-solving-based learning models, and metaphorical thinking approaches are proposed as potential solutions. These strategies are considered effective in enhancing students’ conceptual understanding and scientific reasoning abilities when implemented appropriately. The findings provide valuable insights for educators to design more targeted instructional interventions and contribute to improving learning outcomes in physics education, particularly in Newtonian mechanics.